2020
DOI: 10.3390/agronomy10081100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Ground Magnesium Limestone Application, with or without Bio-Fertilizer Addition, on Biochemical Properties of an Acid Sulfate Soil and Rice Yield

Abstract: A study was conducted to evaluate the effects of applying rice husk biochar (RHB) or ground magnesium limestone (GML) in combination with bio-fertilizer on soil biochemical properties and the yield of rice planted on an acid sulfate soil. The RHB or GML plus bio-fertilizer were applied each at the rate of 4 t ha−1. Applying the amendments increased soil pH (>5.0) and improved soil biochemical properties with a concomitant reduction of Al and Fe that resulted in enhanced rice growth. Applying GML plus bio-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…This mechanism is less important for this study since freshly prepared biochars with larger particle sizes were applied. Our result was in line with Panhwar et al [57], where they found 99.82% increased available P using biochar and bio-fertilizer.…”
Section: Biochar and Lime Treatment Affects Soil Propertiessupporting
confidence: 93%
“…This mechanism is less important for this study since freshly prepared biochars with larger particle sizes were applied. Our result was in line with Panhwar et al [57], where they found 99.82% increased available P using biochar and bio-fertilizer.…”
Section: Biochar and Lime Treatment Affects Soil Propertiessupporting
confidence: 93%
“…This unique combination of bioactive organic compounds, carbonate minerals, and nanoporosity makes crab shells an attractive complex natural product for various niches of agricultural applications or other smart biocomposites for wider applicability, as previously described [ 4 ]. Specifically related to agriculture, Panhwar et al [ 7 ] argued that the amendment of rice farming soil with ground magnesian limestone in combination with an organic fertilizer acted to elevate the soil pH, and exchangeable Ca and Mg nutrients, which in turn enhanced the plant growth. This observation [ 7 ] opens the avenue for the use of crab shells for fertilizing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically related to agriculture, Panhwar et al [ 7 ] argued that the amendment of rice farming soil with ground magnesian limestone in combination with an organic fertilizer acted to elevate the soil pH, and exchangeable Ca and Mg nutrients, which in turn enhanced the plant growth. This observation [ 7 ] opens the avenue for the use of crab shells for fertilizing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Constraints faced on dryland and swampland include low soil pH, low availability of nutrients, and high soil Fe content ( [10,11,12,13]. In paddy fields, the problem faced is a decrease in land productivity due to inappropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that low soil pH had an impact on reducing maize yields by 11-37% [15], and rice yields from 14.52-28.97% [16]. Rice productivity in acid soils can be increased, among others, through the application of lime [17], and the application of Ground Magnesium Limestone (GML) in combination with a biofertilizer [13].…”
Section: Introductionmentioning
confidence: 99%